2008
DOI: 10.1002/nau.20582
|View full text |Cite
|
Sign up to set email alerts
|

Management of neurogenic bladder patients in the Netherlands: do urologists follow guidelines?

Abstract: The majority of Dutch urologists is involved in the treatment of neurogenic bladder, which suggests a less prominent role for specialized centers. Furthermore, urodynamics are not performed routinely. These observations are contrary to the recommendations of the available guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 9 publications
(12 reference statements)
1
17
0
2
Order By: Relevance
“…A higher proportion of participants receiving routine urological checkups was expected based on a survey among Dutch urologists. 19 In this survey, 84% of the urologists claimed to perform routine follow-up in patients with NLUTD every 6 or 12 months. 19 Possible explanations for this apparent discrepancy are that some participants might not have been referred to a urologist at all or that some participants may have been noncompliant with scheduled follow-up contacts.…”
Section: Urological Surveillancementioning
confidence: 92%
See 1 more Smart Citation
“…A higher proportion of participants receiving routine urological checkups was expected based on a survey among Dutch urologists. 19 In this survey, 84% of the urologists claimed to perform routine follow-up in patients with NLUTD every 6 or 12 months. 19 Possible explanations for this apparent discrepancy are that some participants might not have been referred to a urologist at all or that some participants may have been noncompliant with scheduled follow-up contacts.…”
Section: Urological Surveillancementioning
confidence: 92%
“…19 In this survey, 84% of the urologists claimed to perform routine follow-up in patients with NLUTD every 6 or 12 months. 19 Possible explanations for this apparent discrepancy are that some participants might not have been referred to a urologist at all or that some participants may have been noncompliant with scheduled follow-up contacts. Factors identified as being associated with noncompliance are costs, distance, transportation, time, and the belief that follow-up was not necessary.…”
Section: Urological Surveillancementioning
confidence: 92%
“…In the Netherlands, a survey of urologists found that only 18% followed the EAU guideline frequently when treating patients with NGB, 35% occasionally and 47% not at all. Only 12% performed the recommended annual urodynamics 14 .…”
Section: Commentmentioning
confidence: 99%
“…Cette prise en charge par l'urologue ou le médecin MPR, est une spécificité française. Aux Pays-Bas et au Canada, ces patients sont pris en charge uniquement par des urologues [5,6]. Il convient d'éviter que la prise en charge des patients par deux spécialités e600 questionnaires were sent to the members of four scientific societies.…”
Section: Résuméunclassified
“…Les questions et/ou choix de réponses différaient selon les spécialistes (voir questionnaires en complément électronique). Le questionnaire a été inspiré de ceux utilisés par les urologues canadiens [6] ou néerlandais [5]. En plus des questions d'ordre général (démographie et type de pratique), le questionnaire comportait des questions sur la cause, l'organisation de la consultation, les modalités du suivi systématique, la gestion des bactériuries, des infections urinaires symptomatiques et des différents types de dysfonctions vésico-sphinctériennes d'origine neurologique.…”
Section: Méthodesunclassified